Visual properties and memorising scenes: Effects of image-space sparseness and uniformity - Lukavský, Jiří; Děchtěrenko, Filip (Attention, perception & psychophysics, 2017)
Previous studies have demonstrated that humans have a remarkable capacity to memorise a large number of scenes. The research on memorability has shown that memory performance can be predicted by the content of an image. We explored how remembering an image is affected by the image properties within the context of the reference set, including the extent to which it is different from its neighbours (image-space sparseness) and if it belongs to the same category as its neighbours (uniformity). We used a reference set of 2,048 scenes (64 categories), evaluated pairwise scene similarity using deep features from a pretrained convolutional neural network (CNN), and calculated the image-space sparseness and uniformity for each image. We ran three memory experiments, varying the memory workload with experiment length and colour/greyscale presentation. We measured the sensitivity and criterion value changes as a function of image-space sparseness and uniformity. Across all three experiments, we found separate effects of 1) sparseness on memory sensitivity, and 2) uniformity on the recognition criterion. People better remembered (and correctly rejected) images that were more separated from others. People tended to make more false alarms and fewer miss errors in images from categorically uniform portions of the image-space. We propose that both image-space properties affect human decisions when recognising images. Additionally, we found that colour presentation did not yield better memory performance over grayscale images.
Keywords: Mental Recall; Scene perception; Pattern Recognition, Visual; Humans; Recognition, Psychology; lidé středního věku; paměť; neuronové sítě; Female; dospělí; Neural Networks, Computer; lidé; Photic Stimulation; světelná stimulace; rozpomínání; rozpoznávání obrazu; Adult; ženské pohlaví; Male; Middle Aged; rozpoznávání (psychologie); Categorization; Memory; Memory: visual working and short-term memory; mužské pohlaví